Homogeneous Catalytic Oxidation of Olefins with Hydrogen Peroxide in the Presence of a Manganese-Substituted Polyoxomolybdate - Duarte, Tiago A. G.
[PMo11Mn(H2O)O-39](5-) is used as catalyst in the homogeneous oxidation of cis-cyclooctene, cyclohexene, styrene, and geraniol with H2O2 in acetonitrile. Oxidation of cis-cyclooctene gives only cyclooctene oxide; cyclohexene-1,2-diol is the main product for cyclohexene; styrene is preferentially oxidized to benzaldehyde; a TOF almost as high as 28800 h(-1) is reached for geraniol oxidation.